Creating communities and communicating science during COVID-19: From Coast2Coast to Coast2Cast. (1st August 2022) - Vila-Concejo, Ana; Splinter, Kristen D.; Harley, Mitchell D.; Lowe, Ryan; Fellowes, Thomas E.; McCarroll, R. Jak; Coco, Giovanni
Abstract: The global COVID-19 pandemic has seen extended lockdowns, isolation periods and travel restrictions across many countries around the world since early 2020. Some countries, such as Australia and New Zealand, closed their international borders in early 2020 preventing researchers travelling to other parts of the world. To facilitate the exposure of our students' work, and for them to meet international researchers, as well as foster a sense of coastal community, we started a zoominar series (seminars via Zoom) in April 2020. The Coast2Coast zoominar series had therefore humble origins but we soon discovered that there was an appetite for more widely sharing science across the coastal research disciplines. The Coast2Coast zoominar grew rapidly, attracting researchers from many countries around the world who presented and attended fortnightly online seminars. In just one year and a half we had 38 presentations with roughly 1900 attendees, creating a sense of community and belonging for the researchers involved. In early 2021, two of the co-authors, Giovanni (GC) and Ana (AVC) decided to expand and take this sense of community further creating the Coast2Cast podcast series, where researchers are asked research and non-research questions. In only 7 months, the podcasts have attracted more than 3700 listeners. Importantly, while the main prerequisite was high-quality and impactful research, diversity and inclusion were also a priority in selecting and inviting speakers for the zoominars and guests for the podcast. Importantly, our survey results suggest that there is a place for online events similar to Coast2Coast and Coast2Cast in a pandemic-free future, and that the coastal community involved has greatly benefited from such initiatives. Highlights: Two new online initiatives provided unexpected benefits during the COVID-19 pandemic. Both initiatives contributed to creating a sense of community and belonging for the researchers involved. The main prerequisite was high-quality and impactful research. Diversity and inclusion were considered a priority, thus increasing diversity and inclusion. Our results suggest that there is a place for short online events in a pandemic-free future.